Visible light-induced PET-RAFT polymerization of methacrylates with novel organic photocatalysts. Issue 39 (3rd May 2017) - Tu, Kai; Xu, Tianchi; Zhang, Lifen; Cheng, Zhenping; Zhu, Xiulin
Abstract : PET-RAFT polymerization was successfully carried out under irradiation of various LED lights at room temperature by using two novel organic agents 4-methoxybenzaldehyde and 2, 4, 6-tri-( p -methoxyphenyl) pyrylium tetrafluoroborate for the first time. Abstract : Light-emitting diode (LED) technology in the visible spectrum holds great promise for photopolymerization because of its characteristic virtues such as low energy consumption, no ozone release, low heat generation, simple and safe operation, high performance, etc. In this work, two organic agents, 4-methoxybenzaldehyde (PC1) and 2, 4, 6-tri-( p -methoxyphenyl) pyrylium tetrafluoroborate (PC2), were employed as the photocatalysts for the photoinduced electron transfer-reversible addition–fragmentation chain transfer (PET-RAFT) polymerization under irradiation of various LED lights (purple, blue and white LEDs) at room temperature, using methyl methacrylate (MMA) as the model monomer and typical 2-cyanoprop-2-yl 1-dithionaphthalate (CPDN) as the RAFT agent. It has been found that the polymerization could be carried out smoothly with a wide range of wavelengths of visible light and could be extended to other methacrylates such as ethyl methacrylate (EMA) and n -butyl methacrylate ( n -BMA). In addition, the "living" feature of this polymerization system was demonstrated by its polymerization kinetics and was confirmed by a chain-extension experiment.